Statin Treatment as a Targeted Therapy for APC-Mutated Colorectal Cancer - Shailes, Hannah; Tse, Wai Yiu; Freitas, Marta O.; Silver, Andrew; Martin, Sarah A. (Frontiers in Oncology, 2022)
Background: Mutations in the tumour suppressor gene Adenomatous Polyposis Coli (APC) are found in 80% of sporadic colorectal cancer (CRC) tumours and are also responsible for the inherited form of CRC, Familial adenomatous polyposis (FAP). Methods: To identify novel therapeutic strategies for the treatment of APC mutated CRC, we generated a drug screening platform that incorporates a human cellular model of APC mutant CRC using CRISPR-cas9 gene editing and performed an FDA-approved drug screen targeting over 1000 compounds. Results: We have identified the group of HMG-CoA Reductase (HMGCR) inhibitors known as statins, which cause a significantly greater loss in cell viability in the APC mutated cell lines and in in vivo APC mutated patient derived xenograft (PDX) models, compared to wild-type APC cells. Mechanistically, our data reveals this new synthetic lethal relationship is a consequence of decreased Wnt signalling and, ultimately, a reduction in the level of expression of the anti-apoptotic protein Survivin, upon statin treatment in the APC-mutant cells only. This mechanism acts via a Rac1 mediated control of beta-catenin. Conclusion: Significantly, we have identified a novel synthetic lethal dependence between APC mutations and statin treatment, which could potentially be exploited for the treatment of APC mutated cancers.